Firm’s technological capabilities towards technology transfer performance in Malaysian manufacturing companies: The antecedents that lead to successful development of firm’s technological capabilities - Md Hasan, Siti Aishah; Ibrahim, Abdullah (Penerbit Universiti Malaysia Pahang, 2022)
Drawing upon Resource-Based View (RBV) theory, this research investigates the effect of technological capabilities on the performance of technology transfer activities in Malaysian manufacturing firms. This research also empirically examines the antecedents that lead to the development of a firm’s technological capabilities. The data were obtained from 133 manufacturing companies in Malaysia by means of questionnaires. As predicted, the results indicated that the firm’s technological capabilities significantly related to technology transfer performance and all the antecedents are chosen positively influenced the firm’s technological capabilities development.